The embryo and the endosperm contribute equally to argan seed oil yield but confer distinct lipid features to argan oil - Errouane, Kheira; Doulbeau, Sylvie; Vaissayre, Virginie; Leblanc, Olivier; Collin, Myriam; Kaid-Harche, Meriem; Dussert, Stéphane (Food chemistry, 2015)
•The argan seed is made of two well-developed tissues: the embryo and the endosperm.•The embryo and the endosperm store the same amount of lipids.•Tocopherol content of the endosperm was markedly higher than that of the embryo.•The fatty acid composition of the two seed tissues differs considerably.•The endosperm and embryo have similar sterol and triterpene alcohol composition. In the perspective of studying lipid biosynthesis in the argan seed, the anatomy, ploidy level and lipid composition of mature seed tissues were investigated using an experimental design including two locations in Algeria and four years of study. Using flow cytometry, we determined that mature argan seeds consist of two well-developed tissues, the embryo and the endosperm. The lipid content of the embryo was higher than that of the endosperm, but the dry weight of the endosperm was higher. Consequently, both tissues contribute equally to seed oil yield. Considerable differences in fatty acid composition were observed between the two tissues. In particular, the endosperm 18:2 percentage was twofold higher than that of the embryo. The tocopherol content of the endosperm was also markedly higher than that of the embryo. In contrast, the endosperm and the embryo had similar sterol and triterpene alcohol contents and compositions.